Observational Study on the Characteristics of the Boundary Layer during Changes in the Intensity of Tropical Cyclones Landing in Guangdong, China - Fei Liao; Ran Su; Pak-Wai Chan; Yanbin Qi; Kai-Kwong Hon (Advances in Meteorology)
Eleven tropical cyclones that landed in Guangdong Province since 2012 and experienced strengthening or weakening over the offshore area were studied. Since the structure of the tropical cyclone boundary layer significantly influences the variation of the intensity of the cyclone, continuous observations of the wind profile radar at a coastal radar station in Guangdong Province were combined with aircraft observation data of the No. 1604 “Nida” cyclone to analyse the variations in the distributions of the radial wind, tangential wind, and angular momentum in the typhoon boundary layer and the similarities and differences between the boundary layers of the 11 tropical cyclones during the strengthening or weakening of their intensities. The analysis results show that the presence of the supergradient wind and the enhancement effect of the radial inflow play important roles in enhancing the intensity of a tropical cyclone. The observations indicate that when the tangential wind velocity in the maximum wind velocity radius reaches the velocity of the supergradient wind and when the radial inflow either gradually increases towards the centre of the tropical cyclone or gradually covers the entire boundary layer, the angular momentum tends to be shifted towards the centre. At this time, the maximum radial inflow, maximum tangential wind, and maximum angular momentum are in the same height range in the vertical direction. When a strong radial outflow occurs in the boundary layer of a tropical cyclone or the area with maximum wind velocity is located in the air outflow, the angular momentum cannot easily be transported towards the centre of the typhoon. Therefore, the spatial configuration of the three physical quantities will determine future changes in the intensity of tropical cyclones. The scope of the results presented here is limited to the 11 selected cases and suggests extending the analysis to more data.